FAKTOR DETERMINAN MINAT BERWIRAUSAHA MAHASISWA (EVALUASI PEMBELAJARAN KEWIRAUSAHAAN DI PERGURUAN TINGGI PERIKANAN DAN KELAUTAN) - Muh Ikramullah; Aslinda Aslinda; Heriansah Heriansah (Universitas Sebelas Maret, 2020)
Entrepreneurship learning in higher education has a strategic role in developing students' interest in entrepreneurship. This study aims to determine the determinant factors of student interest in entrepreneurship as an evaluation material for entrepreneurship learning, especially in fisheries and marine colleges. This study uses a quantitative approach through descriptive correlational methods. The number of respondents was 110 students of the College Marine Technology of Balik Diwa Makassar. The data were collected through a questionnaire instrument using a Likert scale and analyzed using multiple regression analysis. The results showed that 43.6% of students' interest in entrepreneurship was simultaneously influenced by factors of income expectations (X1), family support (X2), and entrepreneurial learning (X3). The regression equation for student interest in entrepreneurship is Y = 1.112 + 0.302X1 + 0.736X2 + 0.284X3. Income expectations and family support as well as entrepreneurial learning together influence respondents' interest in entrepreneurship (P <0.05). Entrepreneurship learning provided the lowest contribution to student entrepreneurial interest. Learning methods and facilities need special attention in increasing student entrepreneurial interest. These entrepreneurial learning methods and facilities must be able to develop entrepreneurial spirit and activities based on family environment activities supported by science and technology.Keywords: entrepreneurship learning, family environment, fisheries and marine, income expectations, interest in entrepreneurship